Comparing Two Improved Techniques With the Traditional Surgical Techniques for Intra and Extramedullary Spinal Tumor Resection: A Report of 280 Cases - Djumanov, Kamaliddin; Kariev, Gayrat; Chmutin, Gennady; Antonov, Gennady; Chmutin, Egor; Musa, Gerald; Maier, Adam; Shumadalova, Alina (Frontiers in Surgery, 2022)
Objectives Spinal tumors remain a challenging problem in modern neurosurgery. The high rate of postoperative morbidity associated with intramedullary tumors makes the need for safer surgical techniques invaluable. This study analyses our experience with the treatment of spinal cord tumors and compares traditional management and a new different surgical approach to intramedullary tumors with an associated hydrosyringomyelia. Materials and Methods This retrospective study compared standard surgical techniques and 2 newer modified techniques for intra and extramedullary spinal tumors at the Neurosurgery center for spinal cord tumors of the Republic of Uzbekistan. Preoperative neurological status was recorded with the ASIA/ISNCSCI scale. Postoperative outcome was graded using the Nurrick score. Results Of the 280 cases, there were 220 (78.5%) extramedullary and 60 (21.5%) with intramedullary spinal tumors. The control and main group had 159 (56.8%) and 121 (43.2%) patients, respectively. Severe compression myelopathy (ASIA- A, B, C) was 217 (77.5%) patients i.e., ASIA A-39 (13.9%); B-74 (26.4%), and C-104 (37.1%). In 74 extramedullary tumors (33.6%) treated with the new method, good postoperative outcomes in 44 cases (59.5%) with OR = 1.9; 95% CI 1.1–3.3 (p < 0.05). Thirty-seven (61.7%) intramedullary tumors were treated with the newer modified technique. There was no difference with the standard method (p = 0.15). However, when comparing postoperative Nurick grade 1–2 with grade 3–4, the newer strategy was superior with improvement in 24 (65%) patients, OR = 3.46; 95% CI 1.2–10.3 (p < 0.05). Conclusion When compared with standard methods, the proposed newer modified strategy of surgical treatment of spinal cord tumors with the insertion of a syringosubarachnoid shunt in the presence of an associated hydrosyringomyelia is associated with better postoperative outcome (Nurick 1 and 2) in 64.8%.